2010
DOI: 10.4049/jimmunol.0901208
|View full text |Cite
|
Sign up to set email alerts
|

A CD1d-Dependent Antagonist Inhibits the Activation of Invariant NKT Cells and Prevents Development of Allergen-Induced Airway Hyperreactivity

Abstract: The prevalence of asthma continues to increase in westernized countries, and optimal treatment remains a significant therapeutic challenge. Recently, CD1d-restricted invariant NKT (iNKT) cells were found to play a critical role in the induction of airway hyperreactivity (AHR) in animal models and are associated with asthma in humans. To test whether iNKT cell-targeted therapy could be used to treat allergen-induced airway disease, mice were sensitized with OVA and treated with di-palmitoyl-phosphatidyl-ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…On the other hand, neither OVA-induced airway inflammation nor AHR were inducible in iNKT cell-deficient mice, indicating an important causative role for these cells [334]. These observations were supported by experiments applying anti-CD1d antibodies to animals and by treatment with CD1d-dependent antagonists, both suppressing OVA-induced AHR and inflammation [333,342]. Of note, Akbari et al [343] demonstrated that more than half of the pulmonary CD4 + cells in human bronchial asthma belong to the iNKT lineage.…”
Section: Contribution Of Nk T Cells To Allergic Immune Responsessupporting
confidence: 59%
“…On the other hand, neither OVA-induced airway inflammation nor AHR were inducible in iNKT cell-deficient mice, indicating an important causative role for these cells [334]. These observations were supported by experiments applying anti-CD1d antibodies to animals and by treatment with CD1d-dependent antagonists, both suppressing OVA-induced AHR and inflammation [333,342]. Of note, Akbari et al [343] demonstrated that more than half of the pulmonary CD4 + cells in human bronchial asthma belong to the iNKT lineage.…”
Section: Contribution Of Nk T Cells To Allergic Immune Responsessupporting
confidence: 59%
“…Recently, a CD1d-dependent antagonist, dipalmitoyl phosphatidylethanolamine polyethylene glycol, has been shown to inhibit NKT cells and suppress AHR (55). However, dipalmitoyl phosphatidylethanolamine polyethylene glycol had no effect on the development of OVA-specific Th2 responses.…”
Section: Discussionmentioning
confidence: 97%
“…A CD1d-binding lipid antagonist prevented AHR in a murine model of allergen challenge but had no effect on T H 2 cells. 81 Interestingly, CD1d-restricted NKT cell clones recognized phospholipids from cypress pollens, although more phospholipid-responsive clones were conventional CD4 1 T cells or gd T cells. 82 gd T cells use a T-cell receptor comprising g and d chains as opposed to the classical ab T-cell receptor found on most CD4 1 T cells.…”
Section: Other T Cells: Cd8 T Cells Nkt Cells and Gd T Cellsmentioning
confidence: 98%